The Relationship between Self Management and Quality of Life of Type 2 Diabetes Mellitus Patients in the Telaga Health Center Work Area through Dorothea Orem's Self Care Approach - Pomalango, Zulkifli B.; Basir, Ita Sulistiani; Arsad, Sitti Fatimah Meylandri; Mursyidah, Andi (Jambura Nursing Journal, 2026)
Diabetes mellitus is a disease that can cause complications in various organs of the body so that it requires long-term treatment. Inadequate management causes sufferers to experience complications that can affect their quality of life. The impact on quality of life can be minimized through self-management. The decrease in quality of life in diabetes mellitus patients is also often accompanied by the patient's inability to carry out self-care independently, which is known as self-care. The aim of the research is to determine the relationship between self-management and the quality of life of Type 2 diabetes mellitus patients in the Telaga Community Health Center working area through Dorothea Orem's self-care approach. The population in this study was 194 Diabetes Mellitus patients. The sample in the study consisted of 66 respondents using a purposive sampling technique. The research instrument used the Diabetes Quality of Life (DQOL) questionnaire, the DSMQ (Diabetes Self Management Questionnaire) questionnaire. The results of this study show a p-value of 0.031 so it can be concluded that there is a significant relationship between self-management and the quality of life of Type 2 diabetes mellitus patients in the Telaga health center working area through the Dorothea Orem self-care approach.